ANALISIS PERENCANAAN PAJAK (TAX PLANNING) PADA PT PRATAMA GRAHA SEMESTA - Fitri Rahmiyatun; Sugiarti Sugiarti; Rina Oktiyani; RM Teddy Aliudin; Merlyn Merlyn (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2023)
According to Law Number 36 of 2008 there are two Tax Subjects, namely, Domestic Tax Subjects (SPDN) and Foreign Tax Subjects (SPLN). One of the Domestic Tax Subjects is a Business Entity that has the largest contribution in tax revenue. The tax that must be paid by the Business Entity depends on the profit it generates each year. The higher the profit, the higher the tax. Therefore, to minimize tax payments according to the rules of the taxation frame, Tax Planning is needed, namely several ways to minimize the tax burden without having to violate the tax law. In writing this final project, two methods are used, namely the Observation Method and the Documentation Method. The data used are the Income Tax Return, VAT, and the Financial Statements of PT Pratama Graha Semesta 2020. The results of this final project research, Tax Planning at PT Pratama Graha Semesta utilizes the Government Borne Income Tax (DTP) incentive according to PMK 09/PMK.03 /2021 such as PPh Article 21, PPh Article 22 Imports, Reduction in Installment of PPh Article 25 by 50%, optimizing credit for input tax invoices through the e-invoice application on the Prepopulated VAT menu, collecting evidence of withholding income tax, minimizing the tax burden on Article 23 PPh, avoiding sanctions fines by setting the payment date and separate tax reporting, as well as conducting fiscal reconciliation. So with Tax Planning, tax financing can be well organized.